Proyek Residivis Berbasis Pencarian dengan Bantuan Komputer (CAS) Computer Asisted Search - Faradillah Firdaus; Muh Alif Akbar; Astrid Ariska; Khusnul Khatimah; Jhinan Putri Sephinan (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2024)
Bapas makassar plays a crucial role in carrying out its duties, particularly through the implementation of Community Research (Litmas). Litmas has a significant positive impact in supporting the stages of the criminal justice system. Data from Litmas serves as a vital instrument for the rehabilitation of Inmates, ensuring the smooth process of Assimilation or Social Integration. Prior to conducting Litmas, client data search is essential to determine their recidivism status. Recidivism is defined as an individual's tendency to repeat reprehensible acts after being sentenced. Despite having recidivism data from 2010 to 2021 in hard file format, BAPAS Makassar faces security and data retrieval challenges. Hence, the implementation of a digital-based recidivism program becomes a solution to enhance efficiency and data security. The project's execution takes approximately two months with a team consisting of four members from the Project BKP Humanitarian Office at the Makassar Class I Correctional Institution. The BAPAS Makassar project leverages information technology and criminal database systems to efficiently manage information related to recidivism. The main advantage of this project lies in the ease of accessing recidivism data for inmates, and the digital-based security ensures data integrity.